Children & Migration: Political Constructions and Contestations. (27th September 2021) - Pruitt, Lesley J.
Abstract: This article demonstrates the importance of paying attention to the roles children and childhood play in policy making relating to migration, especially since the outcomes of these debates have serious implications for children and for migrants, refugees, and asylum seekers of all ages. The article considers a case study examining political representations of migrant, asylum seeker, and refugee children from 2015 to 2016 in the United Kingdom Parliament. Applying discourse analysis to Hansard records, the article demonstrates how across significant political differences, policy makers come together in painting children as victims in need of urgent protection while situating themselves and the UK as best placed to determine how to provide this security to the children in question – historically, currently, and in the future. In doing so, policy makers contribute to inaccurate essentialisations of children, and simultaneously situate the UK as a global protector of children, even when limited agreement on policy approaches exists. Abstract : While emotion‐laden, simplified images drawing on common stereotypes of children as victims may seem a quick, effective way to bolster support for a given policy, policy makers seeking to enhance children's security should recognise that such representations may simultaneously exclude important considerations of children's views, participation, and needs.